The Analysis of Ability and Willingness to Pay of Inpatients in Kapal Badung Hospital - Waty, Putu Linda Astrini (Community Health)
The Kapal Badung district hospital has become a class C hospital with a status as district public service body since late 2010. The hospital revenue had increased during year 2009 to 2011, yet the hospital is still subsidized by the government. Therefore, in its development, the hospital is expected to be able to do tariffs improvement, which is influenced by ability and willingness to pay for health care. The aim of this research is to measure the ability and willingness to pay of inpatient services in the Kapal Badung Hospital. This research was descriptive which describes ability and willingness to pay of inpatients in the Kapal Badung Hospital. The design employed in this research was cross-sectional in which the measurement was conducted at a point in time. The number of sample in this research was 261 persons. The average of third class patients’ willingness to pay was Rp. 279.985; second class was Rp. 297.995; first class was Rp. 443.557, and VIP class was Rp. 950.796. Meanwhile, the ability to pay of the third class patients was Rp. 22.777; second class was Rp. 42.500; first class was Rp. 42.500, and VIP class was Rp. 241.667. Generally, the ability to pay of the first, second, third and VIP classes were higher than the prevailing tariffs. Community’s willingness to pay for in-patient services in the Kapal Badung Hospital for the second, third and VIP classes were lower than tariffs, nevertheless the willingness to pay of the first class patients was higher than the prevailing tariff.